2007
DOI: 10.1074/jbc.m702952200
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of MsbA from Pseudomonas aeruginosa

Abstract: Lipopolysaccharide of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…In addition, MsbA increases resistance to erythromycin by 86-fold when it is expressed in L. lactis [22]. In contrast, expression of MsbA in Pseudomonas aeruginosa did not confer resistance to erythromycin, but introducing E. coli msbA into P. aeruginosa decreased the susceptibility of this bacterium to erythromycin by 4-fold [46]. Hence, we investigated whether the isogenic msbA mutant was more sensitive to erythromycin than wild-type H. pylori .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, MsbA increases resistance to erythromycin by 86-fold when it is expressed in L. lactis [22]. In contrast, expression of MsbA in Pseudomonas aeruginosa did not confer resistance to erythromycin, but introducing E. coli msbA into P. aeruginosa decreased the susceptibility of this bacterium to erythromycin by 4-fold [46]. Hence, we investigated whether the isogenic msbA mutant was more sensitive to erythromycin than wild-type H. pylori .…”
Section: Resultsmentioning
confidence: 99%
“…The truncated LPS was isolated primarily in the IM fraction, and the apparent lengthening of the IM is more consistent with specific IM localization. P. aeruginosa lipid A-core chemically stripped of all phosphates (including the lipid A phosphates) failed to stimulate the ATPase activity of isolated P. aeruginosa MsbA in vitro (16), but this could not be attributed to a particular phosphate(s). In our electron micrographs, there was no obvious blebbing on the inner leaflet of the IM previously seen with MsbA temperature-sensitive mutants of E. coli (20).…”
Section: Discussionmentioning
confidence: 99%
“…The process emerging has several interesting features; lipid A-core, synthesized on the inner leaflet of the inner membrane (IM), is flipped across the IM by the ATP-binding cassette (ABC) transporter MsbA (16, 17). On the periplasmic side, LPS is first extracted from the outer leaflet of the IM by LptC in coordination with the LptBFG transporter complex and then conveyed by the periplasmic protein LptA to the LptDE complex, which inserts fully assembled LPS to the outer leaflet of the OM through an as-yet-uncharacterized process (13, 18).…”
Section: Introductionmentioning
confidence: 99%
“…Attempted mutant studies determined that msbA is essential for in E. coli (Zhou et al, 1998), and this was independently confirmed in Pseudomonas aeruginosa (Ghanei et al, 2007). Similar studies were conducted in N. meningitidis , with somewhat differing results: total LPS levels for the mutant msbA strain were shown to be lower in the parental strain, indicating the potential presence of a feedback inhibition pathway not seen in E. coli (Tefsen et al, 2005).…”
Section: Lipopolysaccharidementioning
confidence: 97%
“…A growing field of knowledge regarding the trafficking and insertion of bacterial membrane components has succeeded in characterizing the key factors involved in membrane biogenesis in a variety of model systems. The eventual targeting of these essential barriers by molecular inhibitors or using them as vaccine candidates has the potential for inducing either bactericidal effects outright, or increased susceptibility to more established antibiotics (Chiu et al, 2007, 2009; Ghanei et al, 2007). Enzymes/proteins found in the cytoplasm, periplasmic space, and outside the bacterial membrane have all evolved under the confines and conditions of each of these unique microenvironments.…”
Section: Introductionmentioning
confidence: 99%